Factors affecting the predisposition of 'Cabernet Sauvignon' grapevines (Vitis vinifera L.) to the physiological disorder, bunch stem necrosis : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Plant Physiology at Massey University, Palmerston North, New Zealand - Pickering, Andrea Hilary (Massey University, 2006)
Bunch stem necrosis (BSN) is a physiological disorder in grapes. It results in shrivelled berries with poor quality attributes such that wine produced from grapes with high BSN incidence is of compromised quality. Past research has proposed many different hypotheses to explain the disorder. Literature indicates that conditions during certain stages of development may predispose berries to BSN but results are not consistent as to which stage is the critical one or which factors have the most impact. This study was designed to resolve these points of uncertainty. Treatments that either enhanced or decreased vine vigour, or manipulated the light environment around the fruit zone were applied to field grown 'Cabernet Sauvignon' vines over three seasons. Treatments included root pruning, heading back of canes by 50%, laying down a reflective mulch and two 50% shade treatments applied for three weeks either pre- or post-full bloom (FB). A strong positive correlation was found between vine vigour and the incidence of BSN. Three weeks post-FB, during both the current and previous season, was identified as the critical period within which factors predispose bunches to BSN. Plant growth regulators, including GA3, IAA and NPA, were applied to bunches on a different group of field grown vines immediately after FB. Application of GA3 during the critical period, tended to reduce the incidence of BSN, while the effects of IAA and NPA application were less clear and require further research. In a controlled environment (CE) trial, pot-grown vines were placed in CE rooms during one of three development stages. Results showed that treatments applied during the critical threeweek period after FB increased the incidence of BSN three fold compared with no change in BSN incidence for vines that were placed in the CE rooms immediately prior to FB or prior to veraison. Collective results from these studies clearly demonstrate that the period immediately following FB is the most critical time in the predisposition of bunches to BSN. It is suggested that competitive dominance of vegetative growth over the developing inflorescence and bunch for assimilates and/or nutrients may be the predisposing factor/s influencing this disorder.
Keywords: Grape diseases; Grapevines; Viticulture; Fields of Research::300000 Agricultural, Veterinary and Environmental Sciences::300300 Horticulture::300305 Oenology and viticulture